The effect of families' socioeconomic status on the self-concept development of learners. Issue 14 (6th December 2019) - Gasa, Velisiwe; Pitsoane, Enid; Molepo, Lesiba; Lethole, Patricia
ABSTRACT: This article investigates the effect of families' socioeconomic status on the self-concept development of learners. The data were collected using a questionnaire from 31 learners who participated in the community engagement project. During the execution of this project, in addition to assisting learners using self-esteem development intervention methods, certain factors emerged, which apart from the original projects methods for self-concept development, seemed to impact self-concept development. These factors suggested that the school-environment and families' socioeconomic status may additionally influence self-concept development. This was used to conduct the necessary statistical analyses. Findings indicated that there is no significant relationship between the self-concept and any of the three components of the socioeconomic factor. But significant dependencies could be established between isolated elements of the socioeconomic factor and self-concept. A collaboration is, therefore, recommended between parents or guardians, teachers, counsellors and social welfare agencies to cater for the needs of these learners.